2001
DOI: 10.1159/000054008
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glutamatergic and GABAergic Systems in Alcoholism

Abstract: The pharmacological effects of ethanol are complex and widespread without a well-defined target. Since glutamatergic and GABAergic innervation are both dense and diffuse and account for more than 80% of the neuronal circuitry in the human brain, alterations in glutamatergic and GABAergic function could affect the function of all neurotransmitter systems. Here, we review recent progress in glutamatergic and GABAergic systems with a special focus on their roles in alcohol dependence and alcohol withdrawal-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 126 publications
2
46
0
Order By: Relevance
“…The data are consistent with the majority of behavioral pharmacological, electrophysiological, and immunological data demonstrating development of GABA hypofunction with repeated alcohol experience (for reviews, Davis and Wu 2001;Criswell and Breese 2005;Krystal et al 2006). Repeated alcohol administration can alter the expression or function of GABA and serotonin receptor subtypes within the NAC (e.g., Nevo and Hamon 1995;Chen and Lawrence 2000;Papadeas et al 2001;Koob 2003;Thielen et al 2004;Criswell and Breese 2005;Krystal et al 2006).…”
Section: Serotonin and Gaba Responses To Alcohol Depend Upon The Routsupporting
confidence: 82%
“…The data are consistent with the majority of behavioral pharmacological, electrophysiological, and immunological data demonstrating development of GABA hypofunction with repeated alcohol experience (for reviews, Davis and Wu 2001;Criswell and Breese 2005;Krystal et al 2006). Repeated alcohol administration can alter the expression or function of GABA and serotonin receptor subtypes within the NAC (e.g., Nevo and Hamon 1995;Chen and Lawrence 2000;Papadeas et al 2001;Koob 2003;Thielen et al 2004;Criswell and Breese 2005;Krystal et al 2006).…”
Section: Serotonin and Gaba Responses To Alcohol Depend Upon The Routsupporting
confidence: 82%
“…There are 2 major types of neurotransmitter-receptor systems in the CNS: one inhibitory, γ-aminobutyric acid (GABA), and one excitatory, glutamatergic. More than 80% of neurons in the brain use either GABA or glutamate as their neurotransmitters [14,15]. By an unclear mechanism that likely involves neurosteroid modulation and other effects, ethanol acts to increase GABA A receptor-mediated inhibition; but no specific binding site at GABA has yet been identified [14,[16][17][18][19][20].…”
Section: Neurophysiology: Inhibition and Excitationmentioning
confidence: 99%
“…More than 80% of neurons in the brain use either GABA or glutamate as their neurotransmitters [14,15]. By an unclear mechanism that likely involves neurosteroid modulation and other effects, ethanol acts to increase GABA A receptor-mediated inhibition; but no specific binding site at GABA has yet been identified [14,[16][17][18][19][20]. Recent studies have demonstrated that ethanol also acts on a glutamatergic receptor, Nmethyl-D-aspartate (NMDA), by reducing excitatory glutamatergic activity.…”
Section: Neurophysiology: Inhibition and Excitationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the decrease in exploration seen during withdrawal was potentiated in repeated-withdrawal animals treated with Introduction Chronic ethanol treatment leads to adaptive changes in neuronal signalling, frequently leading to heightened excitability (see Little 1999 for review). Although such changes occur in many neurotransmitter systems, alterations in g-aminobutyric acid (GABA) A (Sanna et al 1993;Grobin et al 1998Grobin et al , 2000Papadeas et al 2001;Petrie et al 2001) and N-methyl-d-aspartate (NMDA) receptors (Grant et al 1990;Sanna et al 1993; Davis and Wu 2001;Wilce et al 2001) may be especially important for withdrawal symptomatology. Hypofunction of the GABA A system has long been the therapeutic target for the clinical control of ethanol withdrawal, principally using benzodiazepines such as chlordiazepoxide (Wilbur and Kulik 1981;Nutt et al 1989).…”
mentioning
confidence: 99%